kya jalavaayu parivartan saur badalaav se prabhaavit hota hai? (MAUSAM, 2014)
At present, climate change is a matter of great concern to mankind. This change, which is due to the manmade activities, is changing global temperature and the concentration of CO2 and O3 in the atmosphere. But there are some changes in the sun also. Solar changes could be assessed by solar flux at 10.7cm wavelength. Climate change could be assessed by long time temperature records. In this study we have examined whether solar change has any effect on climate change? We have analyzed two sets of data, 10.7cm solar flux (TSI) and global temperature record, along with total ozone, UV-B flux at ground and satellite data of total solar irradiance. Global temperature anomaly curve (GTAC) shows a slow increase of temperature up to about 1975 and a rapid rise after this year. Solar flux at 10.7cm wavelength shows a decreasing trend up to about 1970 and an increasing trend after this year. It also has 11 year cycle. GTAC, total ozone, UV-flux at ground and TSI also show 11 year cycle and some trend, but none of them matches the long-term trend found in solar flux at 10.7cm wavelength.